Development of 3D Motion Diorama Learning Media to Improve Students’ Critical Thinking Skills - Utami, Putri; Kusumawati, Tri Indah (Journal of Elementary Educational Research, 2025)
The research and development of this 3D motion diorama media is pushed by the low critical thinking ability of grade VI students at SD Negeri 010140 Perkebunan Gunung Melayu. The purpose of this study is to develop teaching materials in the form of 3D motion diorama media about the subject of the solar and lunar eclipse to improve the critical thinking skills of sixth grade students. This research uses the Research and Development (R&D) method with the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model developed by Robert Maribe Brach. The results of the study show that; first, the dioramic media developed was declared very valid by experts, with a media feasibility percentage of 93% along with material feasibility of 94%, while the feasibility of the question instrument was 93%. Assessment by teachers obtained an average of 97% while student assessment obtained an average of 99%. Second, classroom trials showed a significant improvement in students' critical thinking skills, with an average pretest score of 52.7 and post-test score of 91.7 (a difference of 39 points), and an N-Gain of 0.82, indicating a high category. The implications of the use of 3D motion diorama media are also able to improve critical thinking skills. The use of this media in understanding the concept of celestial eclipses also very clearly shows the active involvement of students. This study recommends the application of similar media in sciences subject learning to support the development of students' critical thinking skills in primary school.